Anuria caused by bilateral non-opaque renal calculi - Eckstein, Herbert B.; Oral, Sevinç; Doğramacı, İhsan (The Turkish Journal of Pediatrics, 1958)
A case of anuria due to bilateral pelvi-ureteric obstruction caused by radio-translucent calculi is presented and the diagnostic problems are discussed. We would like to thank our anaesthetists, Dr. Emel Berker and Dr. Gürhan Ünlütürk for their help with the management of this case